Intraclass Correlations for Planning Group Randomized Experiments in Rural Education - Larry V. Hedges; E. C. Hedberg (Journal of Research in Rural Education, 2007)
Experiments that assign intact groups (usually schools) to treatment conditions are increasingly common in educational research. The design of group randomized experiments requires knowledge of the intraclass correlation structure to compute statistical power and to determine the sample sizes required to achieve adequate power. The intraclass correlation structure of academic achievement is shown to be somewhat different in rural schools than in all schools in the nation. This article provides a compilation of intraclass correlation values of academic achievement and related covariate effects that could be used for planning group randomized experiments in rural schools. The use of these values to compute statistical power of group randomized experiments involving rural schools is illustrated.